The Legitimacy of Classical Dance Gagrag Ngayogyakarta - Y. Sumandiyo Hadi (LP2M ISBI Bandung, 2017)
ABSTRACT This article of research findings is to reveal the existence of classical dance style of Yogyakarta, since the government of Sultan Hamengku Buwono I, which began in 1756 lasted up until now on era government of Sultan Hamengku Buwono X. The legitimation of classical dance is considered as